New quantitative method to diagnose coronary in-stent restenosis by 64-multislice computed tomography. Issue 1 (January 2015) - Yoshimura, Masayuki; Nao, Tomoko; Miura, Toshiro; Okada, Munemasa; Nakashima, Yoshiteru; Fujimura, Tatsuhiro; Okamura, Takayuki; Yamada, Jutaro; Matsunaga, Naofumi; Matsuzaki, Masunori; Yano, Masafumi
Abstract Background The aim of this study is to evaluate the accuracy of a newly developed quantitative method using 64-multislice computed tomography angiography (CTA) to detect coronary in-stent restenosis (ISR). Methods and results CTA was performed in 45 patients who underwent stent implantation (79 lesions) and the accuracy to diagnose ISR was evaluated by comparing with invasive coronary angiography (ICA). CTA was evaluated both visually and quantitatively using a new stent restenosis index (SRI) utilizing CT densities at proximal and distal artery lumen from the stented region and the correction value depending on the stent diameter. ICA showed 11 ISR (14%). The sensitivity, specificity, positive predictive value, negative predictive value, and accuracy for visual evaluation were 78%, 75%, 35%, 95%, and 76%, respectively. On the other hand, the quantitative evaluation using SRI represents 82%, 93%, 64%, 97%, and 91%, respectively. Conclusions Evaluation of ISR using SRI is superior to the visual estimation of CTA.